Junie B. double edition! : Junie B., first grader (at last!) ; and Junie B., first grader : toothless wonder - Park, Barbara; Brunkus, Denise; Park, Barbara; Park, Barbara (New York : Scholastic., 2002)
Junie B. Jones learns some interesting things about the Tooth Fairy when she becomes the first student in Room One to lose an upper tooth.
H
b
b